Sub-Acute Thyroiditis presenting as pyrexia of unknown origin, a rare case with literature review - Rubina Mukhtar (Journal of the Pakistan Medical Association, 2022)
Pyrexia of unknown origin (PUO) is a challenging entity in medical practice from a diagnostic point of view. Sub-Acute Thyroiditis (SAT), that is an inflammatory condition of thyroid, self-limiting and easily treatable, is a very rare cause for PUO with a few published cases and unfortunately not considered in routine for the differential diagnosis (DD) of PUO. Usually, it presents with mild thyrotoxicosis signs and symptoms, painful goiter, and rarely with cervical Lymph adenopathy. Thyroid antibodies might be negative, but inflammatory markers are usually raised. Anti-inflammatory drugs (NSAID) and steroids are a simple but very effective treatment. We present our experience for diagnosing and treating a female patient presenting with PUO. She was diagnosed as a case of sub-acute Thyroiditis on nuclear thyroid scan, High resolution ultrasound (HR-USG) of Thyroid and radioimmunoassay (RIA) for thyroid hormones and thyroid antibodies. Continue...